A correlational analysis of tethered swimming, swim sprint performance and dry-land power assessments - Loturco, I.; Barbosa, A. C.; Nocentini, R. K.; Pereira, L. A.; Kobal, R.; Kitamura, K.; Abad, C. C. C.; Figueiredo, P.; Nakamura, F. Y. (International Journal of Sports Medicine, 2016)
Swimmers are often tested on both dry-land and in swimming exercises. The aim of this study was to test the relationships between dry-land, tethered force-time curve parameters and swimming performances in distances up to 200 m. 10 young male high-level swimmers were assessed using the maximal isometric bench-press and quarter-squat, mean propulsive power in jump-squat, squat and countermovement jumps (dry-land assessments), peak force, average force, rate of force development (RFD) and impulse (tethered swimming) and swimming times. Pearson product-moment correlations were calculated among the variables. Peak force and average force were very largely correlated with the 50- and 100-m swimming performances (r=- 0.82 and -0.74, respectively). Average force was very-largely/largely correlated with the 50- and 100-m performances (r=- 0.85 and -0.67, respectively). RFD and impulse were very-largely correlated with the 50-m time (r=- 0.72 and -0.76, respectively). Tethered swimming parameters were largely correlated (r=0.65 to 0.72) with mean propulsive power in jump-squat, squat-jump and countermovement jumps. Finally, mean propulsive power in jump-squat was largely correlated (r=- 0.70) with 50-m performance. Due to the significant correlations between dry-land assessments and tethered/actual swimming, coaches are encouraged to implement strategies able to increase leg power in sprint swimmers.